Hospice care with Traditional Chinese medicine characteristics for a patient with small cell lung cancer with multiple systemic metastases (1例小细胞肺癌伴全身多发转移患者的中医特色安宁疗护) - LU Meiling (卢美玲) (中西医结合护理)
To summarize the experience of hospice care with Traditional Chinese Medicine characteristics in the end-stage of a patient with small cell lung cancer with multiple systemic metastases. By using the concepts, knowledge and skills of hospice care, nursing measures based on the guiding framework of Traditional Chinese Medicine thinking and comfort theory were carried out to help the patient control physical discomfort symptoms, provide psychological, spiritual and social support. Social support and grief counseling were adopted for family members. The hospice care with Traditional Chinese medicine characteristics aims to help the patient die peacefully without pain and with dignity, and help family members smoothed out the grieving process. (本文总结1例小细胞肺癌伴全身多发转移终末期患者中医特色安宁疗护实践经验。运用安宁疗护的理念、知识、技能, 以中医思维及舒适理论为指导框架制定护理措施, 帮助患者控制躯体不适症状, 为其提供心理、精神和社会支持, 同时为家属提供支持和哀伤辅导, 帮助患者无痛苦、有尊严平静离世, 帮助家属平稳度过悲伤期。)